Quarter Life Crisis Dengan Turnover Intention Pada Generasi Z - Arifiani, Zefi Nafira; Ardy Wiratama (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2025)
Turnover intention is an individual's activity of leaving work of his own accord Quarter-life crisis individuals experience fear of facing life in the future. This study uses a quantitative correlational approach. While the independent variable in this study is quarter of life and the dependent variable is turnover instruction. The population in the study was gen z with 50 respondents. The sample was taken by purposive sampling. Data analysis tests used normality and hypothesis tests. The results of this study state that there is a relationship between quarter life crisis and turnover intention in the gen z generation.